Pemanfaatan Digital Marketing Dalam Meningkatkan Penjualan UMKM Di Boyolali - Fahman Hadi; Fataqul Ikhsan Dewantara; Dwi Kharisma Wati (Akmenika: Jurnal Akuntansi dan Manajemen, 2023)
Marketing online is currently in great demand by the public and is one of the media that supports daily operations. Many people are slowly moving from traditional marketing methods to marketing online. Marketing online itself means promoting and promoting a brand or product through the digital world or the internet. Finding and evaluating the advantages of marketing online for boosting MSME sales in Boyolali Regency was the aim of this study. Researchers employed data collection techniques, such as questionnaires and interviews, with SMEs as a sample. The study's target audience consisted of Micro, Small, and Medium-Sized Businesses (MSMEs). Since the study's population is homogeneous, samples can be taken from any population. Using a purposive sample approach, 116 Small, Micro, and Medium-Sized Enterprises (MSMEs) participated in this study as respondents. The instruments used in this study were tested for validity, reliability, and the Classical Assumption Test , autocorrelation test, and heteroscedasticity test) using SPSS version 22. The results of the data analysis were then carried out by hypothesis testing with simple linear regression analysis and T-test to determine the level of closeness of the relationship between the dependent variable and the independent variable.